Effect of Quality and Replacement Rate on the Double Recycled Aggregate Concrete. Issue 1 (February 2020) - Guo, Yuanxin; Li, Qiuyi; Yue, Gongbing; Zheng, Shidong; Wang, Liang
Abstract: Recycled aggregate can be used as a substitute for natural aggregate to produce good regenerated concrete, so the text use recycled coarse aggregate and recycled fine aggregate to substitute for natural aggregate with different replacement rates preparing double recycled aggregate concrete, and researching the effect of the quality and replacement rate of recycled aggregate on the mechanical properties of recycled aggregate systematically. The results show that the compressive strength of double recycled aggregate concrete is increased gradually with the improvement of the quality of recycled aggregate, and the effect from weak to strong is class I, class II and class III. On the other hand, the compressive strength of double recycled aggregate concrete is decreased gradually with the increase of the replacement rate of recycled aggregate, and the maximum reduction is up to 57.2%. Therefore, the simultaneous use of recycled coarse aggregate and recycled fine aggregate have an effect of "double weakening" on the compressive strength of recycled concrete, and it can be applied to the concrete products of low strength grade.